Construction of a circRNA– lincRNA–lncRNA–miRNA–mRNA ceRNA regulatory network identifies genes and pathways linked to goat fertility - Ghafouri, Farzad; Sadeghi, Mostafa; Bahrami, Abolfazl; Naserkheil, Masoumeh; Dehghanian Reyhan, Vahid; Javanmard, Arash; Miraei-Ashtiani, Seyed Reza; Ghahremani, Soheila; Barkema, Herman W.; Abdollahi-Arpanahi, Rostam; Kastelic, John P. (Frontiers in Genetics, 2023)
There is growing interest in the genetic improvement of fertility traits in female goats. With high-throughput genotyping, single-cell RNA sequencing is a powerful tool for measuring gene expression profiles. The primary objective was to investigate comparative transcriptome profiling of granulosa cells of high-and low-fertility goats, using single-cell RNA-Seqseq (scRNA-seq). Thirty samples from Ji'ning gray goats (n=15 for high fertility and n=15 for low fertility) were retrieved from publicly available scRNA-Seq seq data. Functional enrichment analysis and a literature mining approach were applied to explore modules and hub genes related to fertility. Then, interactions between types of RNAs identified were predicted and the ceRNA regulatory network was constructed by integrating these interactions with other gene regulatory networks. Comparative transcriptomics-related analyses identified 150 differentially expressed genes (DEGs) between high-and low-fertility groups, based on fold change (≥<5 and ≤−>5) and false discovery rate (FDR <0.05). Among these genes, 80 were up-regulated and 70 were down-regulated. Also, 81 mRNAs, 58 circRNAs, 8 lincRNAs, 19 lncRNAs, and 55 miRNAs were identified by literature mining. Furthermore, we identified 18 hub genes (SMAD1,